Control of Insect Infestation in Dry Fish by Pyrethrum Treatment on Commercial Containers - T.S., Unnikrishnan Nair; Mathen, Cyriac; P., Ravindranathan Nair (Fishery Technology, 2025)
An efficient method for prevention/control of insect infestation in dry fish by the ap- plication of pyrethrum is described. Three commercial formulations of pyrethrum available in India, namely, Pyrocon E, Pyrethrum EC and Pyrocolloid were found to be equally useful as insect repellants when emulsions of these in water at a concentration of 0.25% pyrethrins were sprayed at the level of 100 ml m" 2 (250 mg m’2), on the exterior of the commercial con- tainers with a polythene lining inside. The treatment prevented insect infestation in commercial dry fish for about three months, whereas the controls got infested within a month. The in- sect-free shelf life for refined and preservative treated dry fish was found to be more than six months when stored in pyrethrum-sprayed containers.